2017
DOI: 10.24966/fsn-1076/100020
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium Exposure Through the Diet

Abstract: Aluminium (Al) is the third most common element in the Earth's crust [1] and is naturally present in the environment. Al is a versatile metal with several properties and has a wide range of uses. Al is used in different alloys with other metals such copper, zinc or magnesium [2].The concentrations of this metal in food and drink have been increasing over time due to the acidification of the soils that transfers the aluminium from the soil to the aquatic environment [3] and anthropogenic activities such as mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…Al is commonly found on Earth. However, due to anthropogenic activities, increasing Al content is observed in food [ 80 ]. Al accumulates in the brain, bones, kidney, and liver [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al is commonly found on Earth. However, due to anthropogenic activities, increasing Al content is observed in food [ 80 ]. Al accumulates in the brain, bones, kidney, and liver [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the mean aluminum content in some food groups. It illustrates that vegetables, fruits, roots and tubers, and seafood are all high in aluminum content (Hardisson et al 2017).…”
Section: Sources Of Aluminummentioning
confidence: 99%
“…In general, the concentration of aluminum in fruits and vegetables depends on different factors, including the acidity of the soil, the water used for irrigation, and the plant variety. As a result of these factors, Hardisson et al (2017) have shown that fruits and vegetables from different origins have different aluminum content. For example, it was reported that an average aluminum content of 32.8 mg/kg was found in bananas from Spain, while bananas from the USA have an aluminum content of 0.4 mg/kg (Soni et al 2001;González-Weller et al 2010).…”
Section: Sources Of Aluminummentioning
confidence: 99%
See 2 more Smart Citations